Barriers to Safe Oxygen Therapy and the Effect of the Training on the Knowledge and Performance of ICU Nurses - Samaneh Mirzaei; Mohsen Gholinataj Jelodar; Shahab Rafieian; Farzaneh Sadat Dehghan; Asma Jaafari Nia; Khadijeh Nasiriani; Amir Neshati (Critical Care Research and Practice)
Introduction. Proper oxygen therapy is crucial in hospitals, particularly intensive care units, to ensure safety and accuracy. The role of nurses during oxygen therapy is vital, as their knowledge and correct performance significantly impact patients’ clinical conditions. A study was carried out to examine the knowledge and performance of nurses regarding safe oxygen therapy. The study aimed to identify the obstacles hindering safe oxygen therapy and assess the impact of training on the knowledge and performance of intensive care nurses. Methods. This study was conducted among the ICU nurses at Shahid Rahnemoun Teaching Hospital in Yazd, Iran. The study method is a sequential combination of descriptive, qualitative, and educational phases. The first stage involved examining the knowledge and performance of 80 ICU nurses in oxygen therapy. The study employed content analysis to elaborate on participants’ perspectives on safe oxygen therapy challenges and potential solutions. The third phase involved a two-group study with pre- and post-tests to examine the effect of training on ICU nurses’ knowledge and performance in oxygen therapy. Results. The study found that intervention and control groups had low average scores in knowledge, performance, and total score of oxygen therapy before the study, with no significant difference. There was a significant difference between intervention and control groups one and three months after the intervention in the areas of knowledge (after-1 month 24.41 vs. 20.29, 95% CI [3.144–5.098], after-3 month 22.13 vs. 20.24, 95% CI [0.729–3.053]), performance (after-1 month 21.54 vs. 18.05, 95% CI [2.898–4.073], after-3 month 19.74 vs. 18.63, 95% CI [0.400–1.824]), and total score of oxygen therapy (after-1 month 45.95 vs. 38.34, 95% CI [6.288–8.925], after-3 month 41.87 vs. 38.87, 95% CI [1.394–4.613]). Conclusion. The study’s findings revealed that nurses in ICUs lack the appropriate knowledge and performance in oxygen therapy. A lack of knowledge and correct practice, insufficient monitoring of oxygen therapy, and defects in hospital equipment are contributing factors. The training was found to improve the knowledge and performance of nurses significantly. Consistent training at shorter intervals is suggested for nurses to keep their knowledge current.